"Not Even a Hospital": Abortion and Identity Tension in Margaret Atwood's Surfacing - Gault, Cinda (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
This article challenges established understandings of Margaret Atwood's Surfacing as a portrait of parallel female and national victimization by focusing on recent theorization of the inherently fraught relationship between national and gendered identities. It addresses the conflicted relationship between national purpose and female autonomy.